Cellular injuries of spray-dried Lactobacillus spp. isolated from kefir and their impact on probiotic properties - Golowczyc, Marina A. (2012)
The injuries caused by spray drying (SD) of three potential probiotic lactobacilli isolated from kefir grains and the impact on some probiotic properties, were evaluated. Results demonstrated that Lactobacillus plantarum 83114 and L. kefir 8321 showed a slight reduction of viability (0.11 and 0.29 log CFU/ml respectively) after SD process, and L. kefir 8348 was found to be more sensitive to the process with a reduction in viability of 0.70 log CFU/ml. Neither membrane damage, evaluated by increased sensitivity to NaCl, lysozyme, bile salt and penicillin G, nor changes in acidifying activity in MRS and milk by lactobacilli were detected after SD. L. plantarum 83114 and L. kefir 8321 after SD did not lose their capacity to adhere to intestinal cells. Nevertheless, L. kefir 8348 showed a significant loss of adhesion capacity after SD. In addition, rehydrated spray-dried L. kefir 8321 retained the ability to protect against Salmonella invasion of intestinal cells. This effect was observed when L. kefir is co-incubated with Salmonella before invasion assay. This work shows that the membrane integrity evaluated by indirect methods and some probiotic properties of lactobacilli isolated from kefir did not change significantly after SD, and these powders could be used in functional foods applications.